Significance of Information Sources to Integrated Pest Management Usage Among Poultry Farmers in Kwara State, Nigeria: Agricultural Technology Transfer - Yekinni, Taofeeq Oyedeji; Adeniyi, Rhoda Titilayo; Ahmed, Kabirat Shola (Jurnal AGRISEP, 2024)
Sources of information on the use of combined pest control measures for a sustainable ecofriendly environment are germane in poultry production. A multistage sampling procedure was used to select 120 respondents using an interview schedule. Data collected on socioeconomic characteristics, sources of information, pest prevalence, constraints, and utilisation of Integrated Pest Management (IPM) in Kwara State were analysed with percentages, frequency, weighted mean score, mean, Chi-square, and Pearson’s Product Moment Correlation at α 0.05. The result shows that respondents were members of the Poultry Association of Nigeria (PAN) (96.7%) with mean age and years of business experience were 43.0±9.9 and 7.3±5.8years respectively. Most of the respondents had tertiary education (84.2%) and produced broilers (51.7%) in four cycles a year (57.5%). The most utilized IPM information sources were from co-farmers (68.3%) and workshops (67.5%); with the most prevalent pest being flies (x̅=1.48) and was low for 54.2% of the respondents.  The respondents’ most utilised IPM method was the prompt elimination of dead birds from the flock (x̅=2.86) which was high for 60%. However, respondents’ most prominent constraint to IPM usage was the government’s insufficient pesticide subsidy (x̅=2.69); and was high for 60.0%. A significant relationship existed between respondents’ IPM usage and sources of information like family (X2=0.938; p=0.005) and internet (X2=1.000; p=0.000); years of education attainment (r=0.022; p=0.021), prevalent pest (r=0.577; p=0.051) and constraints to IPM usage (r=0.186; p=0.012). IPM information sources positively influence its utilisation, hence such sources should be empowered by the relevant stakeholders for a sustainable eco-friendly environment.